Hubungan Alokasi Dana Amil dan Efektivitas Pengelolaan Zakat Dalam Perspektif Hukum Ekonomi Syariah pada Baznas Kota Bandar Lampung - Indah Harum Rezeki; Nasruddin Nasruddin; Muhammad Iqbal Fasa; A. Kumedi Ja’far (LPPM Institut Nasional Laa Roiba Bogor, 2022)
Zakat is an act of worship contained in the pillars of Islam. In the pillars of Islam, tithing is in the third place after prayer. The management of zakat funds aims to increase the usability and efficiency of zakat which has an impact on the realization of justice, community welfare and poverty alleviation in the vicinity. The Amil Fund Allocation in Bandar Lampung City has increased from 2018-2020. In managing the allocation of amil funds, the greater the zakat collection, the greater the allocation of amil rights funds. The research conducted by the author is (Field Research), direct research is carried out in the field using respondent data. Zakat assets funds that occur in BAZNAS Bandar Lampung city have not been maximized for amil rights, because the collection that occurs at BAZNAS Bandar City funds infaq shodaqah is greater than zakat assets. Therefore, to fulfill amil rights, BAZNAS Bandar Lampung City uses infaq shodaqah funds to fulfill amil rights. Keywords: Amil Fund, Zakat Management, Sharia Economic Law